2003
DOI: 10.1103/physrevb.68.094408
|View full text |Cite
|
Sign up to set email alerts
|

Probing a ferromagnetic critical regime using nonlinear susceptibility

Abstract: The second order para−ferromagnetic phase transition in a series of amorphous alloys (F e5Co50N i17−xCrxB16Si12) is investigated using nonlinear susceptibility. A simple molecular field treatment for the critical region shows that the third order suceptibility (χ3) diverges on both sides of the transition temperature, and changes sign at T C . This critical behaviour is observed experimentally in this series of amorphous ferromagnets, and the related assymptotic critical exponents are calculated. It is shown t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 21 publications
3
45
0
Order By: Relevance
“…1 are analyzed according to the Kouvel-Fisher formalism. [87][88][89][90][91][92] This framework allows to obtain a precise estimate of the critical temperature T M C for the transition of the Mo 4+ sublattice, the superscript M referring to the dc magnetometry technique (see the inset of Fig. 3).…”
Section: 76mentioning
confidence: 99%
See 2 more Smart Citations
“…1 are analyzed according to the Kouvel-Fisher formalism. [87][88][89][90][91][92] This framework allows to obtain a precise estimate of the critical temperature T M C for the transition of the Mo 4+ sublattice, the superscript M referring to the dc magnetometry technique (see the inset of Fig. 3).…”
Section: 76mentioning
confidence: 99%
“…[87][88][89][90][91][92] Here, the slope is determined by the critical exponent γ characteristic of the transition, while the relation T * (T M C ) = 0 holds. The expected linear trend is observed in our data for Sm 2 Mo 2 O 7 (see the inset of Fig.…”
Section: 76mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the spin-glass transition can be robustly characterized by a divergence of the cubic component of the magnetization, which occurs at the temperature of spin-glass order [6]. χ nl measurements has been less used for proving ferromagnetic or antiferromagnetic transitions [7], but allows to evidence an incipient magnetic order (Note that this technique is more usually employed for proving a paraelectic to ferroelectric transition, when analyzing the high order harmonics of the electric susceptibility). A particular interest can be found in the case of multicomponent magnetism where, with the linear susceptibility only, it is often difficult to prove a phase coexistence.…”
Section: I/introductionmentioning
confidence: 99%
“…Studies of the critical regimes in La 0.875 Sr 0.125 MnO 3 revealed that the paramagnetic to ferromagnetic phase transition is accompanied by consistent critical exponents belonging to 3D Heisenberg universility class. 22 However, the low temperature transition which received considerable attention in the last decade remains undetermined. The nature of this low temperature phase previously has been interpreted in terms of canted antiferromagnetic phase 1 .…”
Section: Introductionmentioning
confidence: 99%